Clinical Symptoms Prevalence in Patients and its Relation to Variables Associated with Psychotherapeutic Context - Garcia, Horacio Daniel (2019)
Objective. Inquire the prevalence of clinical symptoms in patients and verify possible relationships with some variables linked to the psychotherapeutic context. Method. A quantitative research was designed, at an exploratory level, with a descriptive and correlational design. The Symptom Evaluation Questionnaire (Sandín, Valiente, Chorot, Santed, & Lostao, 2008) and an ad hoc questionnaire were applied to a non-probabilistic sample of 90 subjects (M = 33.80 years, DT = 12.88). Results. There is a marked prevalence of depressive symptoms, anxiety and obsessive-compulsive behaviors; Patients with higher levels of Hostility tend to be linked to younger therapists and remain shorter in treatment; Younger patients tend to show lower levels of Somatization and higher levels of Depression, Interpersonal Sensitivity and Paranoid Ideation. The women obtained higher scores in Somatization, Depression and Phobic Anxiety, while it was found that female therapists tend to assist people with higher levels of Depression, Anxiety and Paranoid Ideation.